Monte Verde and the antiquity of humankind in the Americas - Adovasio, J.M
The Smithsonian Institution Press (with a patience one no longer expects of a scholarly publisher) early this year issued the second volume of Tom Dillehay's monograph on Monte Verde, in far southern Chile Ñ 8 years after the first volume (Dillehay 1989; 1997). What is the standing of the site? Is it the long-sought-after proof of a 'pre-Clovis' human presence in the Americas? And if it is, why is it by the southern tip of the Western Hemisphere, rather than close to its northern portal from Siberia?